Pressure-induced enhancement of thermoelectric performance in palladium sulfide. (June 2018) - Chen, Liu-Cheng; Yu, Hao; Pang, Hong-Jie; Jiang, Bin-Bin; Su, Lei; Shi, Xun; Chen, Li-Dong; Chen, Xiao-Jia
Abstract: Thermoelectric (TE) materials, which can directly convert waste heat into electric power, have attracted considerable interest because of their reliability and great potential for practical applications, especially in the current time faced with energy shortage. Recent advances in developing TE materials for power generation always optimize at high temperatures with the figure of merit ( zT ) above 1. However for the cooling or wearable devices, the high-efficiency TE materials with optimized temperature range near room temperature are strongly in demand. If the optimized TE performance can be tuned from high temperature to around room temperature, the extensive commercial application for microdevices could be expected. Here, we choose polycrystalline palladium sulfide as an example to show that pressure can significantly enhance the TE performance. With the measurements of the resistivity, Seebeck coefficient, and thermal conductivity under pressure up to 10 GPa, a times enhancement of the zT value has been obtained around room temperature. The largest value of zT at high pressures near 10 GPa is comparable to the value at ambient pressure near 800 K. The results indicate that pressure as an irreplaceable thermodynamic variable has positively regulated the TE performance around room temperature. Graphical abstract: Thermoelectric materials with the properties of stability and environmental friendly meet the commercial demand in current time. Recent advances in developing thermoelectric materials for power generation always optimize at high temperatures. Different from the method of warming sample leading to the lattice expansion, applying pressure can bring a times enhancement of thermoelectric figure of merit near room temperature through the lattice compression. The obtained almost same figure of merit by two opposite methods points to the great potential for the further improvement of the thermoelectric efficiency. Image 1 Highlights: This is an innovative research on how applying pressure can tune and improve the thermoelectric (TE) efficiency. A series of high-pressure techniques are developed to investigate the TE properties of a material. Our results indicate that pressure can regulate the TE performance around room temperature.